INTENSI BERWIRAUSAHA MAHASISWA SETELAH MENGIKUTI MATA KULIAH KEWIRAUSAHAAN - Dani Arisandi DN; Wahyu Kumala Sari; Ahmad Akbar Sanjaya (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
Entrepreneurship can be done by all people, including students. Cultivating an entrepreneurial spirit in students in tertiary institutions can be started by fostering a desire and interest in entrepreneurship in students. This study aims to see the interest in entrepreneurship of students who have taken Entrepreneurship courses. The research design used a cross sectional study. Respondents in this study were students in several study programs at the University of Muhammadiyah Papua and the Physics study program at Cenderawasih University. The sampling technique used was proportionate random sampling with a total of 63 people. The analytical method used is descriptive analysis. The results showed that as many as (87%) of respondents stated that they had the desire to run a business in the future. The business interests were grouped based on the distribution of the most desirable including businesses in the Culinary sector (33%), livestock sector (22%), livestock sector (22%) agriculture (16%), tourism (6%), trade (6%), property (4%), services (4%), fisheries (3%), agribusiness (3%) ), and in digital business ventures (1%). Future research is expected to be more aimed at observing behavior and studying more about other aspects related to individual characteristics that are considered to shape student entrepreneurial behavior. Studies of the factors that influence student entrepreneurship interest found in this study need to be studied more deeply, so that a more comprehensive understanding of entrepreneurship can be obtained in students, especially in the field of business they are interested in